Lower molar distalization using clear aligners: Is it effective? A systematic review - Horodynski Martina; A De Stefano Adriana; Bottone Ernesto; Impellizzeri Alessandra; A Vernucci Roberto; Galluccio Gabriella (Wolters Kluwer Medknow Publications, 2024)
Distalization is one of the most useful movements in orthodontic treatments. The aim of this systematic review is to analyze the effectiveness of lower molar distalization using clear aligner therapy (CAT). An electronic search was made from January 2012 to October 2022 using PubMed, Scopus, and LILACS databases without language limitations. This systematic review followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses checklist. The search strategy resulted in 151 studies. A screening was performed to remove duplicates, and all the studies that did not respond to our questions for the title or abstract. Three studies underwent full text analysis. From the evaluation of the studies included in this review, it is possible to state that lower molar distalization is a clinical solution, but it is not a full bodily movement. CAT can provide more specifically a distal tipping movement. This is confirmed analyzing the discrepancy between expected movement and obtained movement. CAT can be considered a valid therapeutic option in patients with dental class III malocclusion, but it is obtained as a tipping movement instead of a body movement. Over-correction should be considered during the planning of the therapy.